Carbon dioxide trends in the mesosphere and lower thermosphere. Issue 4 (1st April 2017) - Qian, Liying; Burns, Alan G.; Solomon, Stanley C.; Wang, Wenbin
Abstract: We investigated trends of carbon dioxide (CO2 ) in the upper atmosphere, using data from the Atmosphere Chemistry Experiment Fourier Transform Spectrometer and from the Sounding of the Atmosphere using Broadband Emission Radiometry. Recent analyses of these measurements had indicated that CO2 above approximately 90 km appeared to be increasing about twice as fast as it was in the lower atmosphere. Models could not reproduce this differential CO2 trend, calculating instead that the proportional CO2 increase is approximately constant with altitude. We found three issues with the methodologies used to derive trends from CO2 profiles: the way that seasonal changes and sampling are accounted for in the analysis, referred to as deseasonalizing; the registration of profiles in pressure versus altitude coordinates; and data quality indicators. Each of these can have significant effects on the derivation of trends. We applied several deseasonalizing procedures, using both pressure and altitude coordinates, also used a time series fit without deseasonalizing, and applied data quality filters. The derived trends were approximately constant with pressure or altitude, about 5.5% per decade, consistent with lower atmosphere CO2 trends, and consistent with model calculations. We conclude that the difference between the trend of CO2 above the CO2 homopause and the trend in the lower, well‐mixed atmosphere is not statistically significant. Key Points: Deseasonalizing methods can have significant effects on the derivation of trends The registration of profiles in pressure versus altitude coordinates and data quality indicators can also affect the derivation of trends The difference between the trend of CO2 above its homopause and the trend in the lower atmosphere is not statistically significant Plain Language Summary: Carbon dioxide (CO2 ) has been increasing in the atmosphere where we live, at an average rate of about 5.5% per decade in the past several decades. This increase of CO2 causes a global warming effect here, but this same increase of CO2 causes a global cooling effect in the space where low Earth orbit satellites fly. Is the rate of CO2 increase the same in the space, or is CO2 increasing twice as fast in the space as it does down here, as suggested by some recent research? This question is important since the rate of CO2 increase determines the rate of cooling it causes in the space. The more cooling, the less drag that space objects encounter; consequently, more space junks accumulate in the space environment. We investigated the rate of CO2 increase in the space based on recent satellite observations. We found that the rate of CO2 increase is approximately constant with altitude, at about 5.5% per decade in the space, the same as the rate of CO2 increase in the atmosphere where we live.